REMOTE WORK AND EMPLOYEE ENGAGEMENT: A GLOBAL PERSPECTIVE ON HRM PRACTICES - Mulia Sosiady; Ermansyah Ermansyah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research aims to examine the relationship between remote work and employe engagement from a global perspective on human resource management (HRM) practices. The study was conducted using the scoping review method on international academic literature and reports from global organizations such as the ILO, Gallup, McKinsey, and Deloitte, published in the last 10 years. The study results indicate that remote work offers benefits such as time flexibility, improved work-life balance, and increased productivity, but also presents challenges including reduced social interaction and potential employe isolation. Digital infrastructure factors have proven to be a determinant of engagement levels, with developed countries supported by technology outperforming developing countries that still face access gaps. Additionally, the role of managers in providing regular feedback, empathy, and emotional support is key to maintaining engagement. Adaptive and inclusive HR practices, such as flexible work hour policies, mental well-being programs, and digital training, have proven effective in boosting employe engagement across diverse cultural contexts. Overall, this study concludes that employe engagement in remote work systems is highly dependent on a combination of digital infrastructure, empathetic leadership, and responsive HR policies. Global organizations need to balance universal values with local adaptation to ensure policies remain relevant across diverse work culture contexts. The practical implications of this research emphasize the importance of flexible, inclusive, and well-being-based HR strategies to maximize the benefits of remote work. This finding is expected to contribute to academic literature and serve as a reference for organizations in developing sustainable remote work policies.